Processing Speaker-Specific Information in Two Stages During the Interpretation of Referential Precedents - Kronmüller, Edmundo; Guerra, Ernesto (Frontiers in Psychology, 2020)
To reduce ambiguity across a conversation, interlocutors reach temporary conventions or referential precedents on how to refer to an entity. Despite their central role in communication, the cognitive underpinnings of the interpretation of precedents remain unclear, specifically the role and mechanisms by which information related to the speaker is integrated. We contrast predictions of one-stage, original two-stage, and extended two-stage models for the processing of speaker information and provide evidence favoring the latter: we show that both stages are sensitive to speaker-specific information. Using an experimental paradigm based on visual-world eye-tracking in the context of a referential communication task, we look at the moment-by-moment interpretation of precedents and focus on the temporal profile of the influence of the speaker and linguistic information when facing ambiguity. We find two clearly identifiable moments where speaker-specific information has its effects on reference resolution. We conclude that these two stages reflect two distinct cognitive mechanisms, with different timings, and that rely on different representational formats for encoding and accessing information about the speaker: a cue-driven memory retrieval process that mediates language processing and an inferential mechanism based on perspective-taking abilities.